(u-3)*8=40

Simple and best practice solution for (u-3)*8=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u-3)*8=40 equation:


Simplifying
(u + -3) * 8 = 40

Reorder the terms:
(-3 + u) * 8 = 40

Reorder the terms for easier multiplication:
8(-3 + u) = 40
(-3 * 8 + u * 8) = 40
(-24 + 8u) = 40

Solving
-24 + 8u = 40

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 8u = 40 + 24

Combine like terms: -24 + 24 = 0
0 + 8u = 40 + 24
8u = 40 + 24

Combine like terms: 40 + 24 = 64
8u = 64

Divide each side by '8'.
u = 8

Simplifying
u = 8

See similar equations:

| y=(-4)-2 | | (q-4)*4=32 | | -16t^2-17t+4=8 | | q=2-(-8) | | q-9=-7 | | (-7)+x=-15 | | 33-X=-2(1+3x) | | 18n^2+27n=0 | | -7(5b-8)+k=239 | | 5cos^2x+4cosx+1=0 | | 32=-4(k-6) | | 7-18=4y-3y+4 | | 3(5x-180+45)=-4(x-72) | | 52x(x-7)=43 | | -2(x+8)=36 | | g(2)+4g-32=0 | | 2-5x+6=14x-32+10(2-x) | | Y=-7/8-9/8 | | X/4-10=-4 | | 6m-13=47 | | (3y+2)+(2y+13)= | | 4x-7-36=0 | | 3m+(5+m)+5= | | 7(5+3r)=203 | | 4y-9=10 | | 4.25/0.75 | | 4x-7+6x=13-10 | | (x+4)(x+5)=1 | | x+10-15=0 | | 14+5x+2x=49 | | 2.840=1.2x-0.2x^2 | | -8y-7=9 |

Equations solver categories